Application and Functional Characterization of Kollicoat Smartseal 30D as a Solid Dispersion Carrier for Improving Solubility - Mehta, Dr. Tejal (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Many new chemical entities that are getting developed are poorly aqueous soluble and have low bioavailability. Out of many methods available for improving solubility, the solid dispersion by melt extrusion (ME) and spray drying (SP) is scalable and industrially applicable methods. Objective: The main objective of the present study was to explore the application of Kollicoat Smartseal 30D polymer for the solubility enhancement of poorly water-soluble drugs using solid dispersion approach. Materials and Methods: The Biopharmaceutical Classification System Class II drug simvastatin (SIM) was used as a model drug in this study. Solid dispersions of SIM and KollicoatÂ® Smartseal 30D were prepared using two different processes, i.e., ME and spray-drying techniques. Both the techniques ME and SP are scalable and industry applicable. Results: The solid dispersion has been characterized using transmission using Fourier transforms infrared spectroscopy, scanning electron microscopy, differential scanning calorimetry, powder X-ray diffraction, saturation solubility, and in vitro drug release studies. Discussion and Conclusion: The improved dissolution profile portrayed the solubility enhancement of SIM in solid dispersions form compared to plain SIM. In nutshell, with the current research, a supportive argument was observed to suggest the suitability of KollicoatÂ® Smartseal 30D based solid dispersions for enhancing solubility of poorly soluble drugs.